Participatory Leadership, Supervision, and Discipline on Employee Performance of Labuhanbatu Regional Development Planning Agency - Muhammad Ardiansah; Pitriyani Pitriyani; Abd. Halim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze participatory leadership, supervision, and discipline on the performance of employees of the Labuhanbatu Development Planning Agency. The data in this study were processed usingIBM SPSS Software.The analytical techniques used include; 1) classic assumption test; 2) multiple linear regression test; 3) hypothesis testing; 4) coefficient of determination. The results of this study indicate that all independent variables have a positive and significant influence on the dependent variable, it can be seen from the value oftcount participatory leadership variable (X1) 5,69 > ttable 1,67with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the participatory leadership variable has a positive and significant effect on employee performance. Marktcount monitoring variable (X2) 4.94 > ttable1.67 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the supervisory variable has a positive and significant effect on employee performance. Marktcount discipline variable (X3) 8.72 > ttable 1.67 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the discipline variable has a positive and significant effect on employee performance. Simultaneously, the variables of participatory leadership, supervision, and discipline have a positive and significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the value of Fcount 53.15 > Ftable 2.77.